Enzyme-Responsive Nanoparticles for Anti-tumor Drug Delivery - Li, Mengqian; Zhao, Guangkuo; Su, Wei-Ke; Shuai, Qi (Frontiers in Chemistry, 2020)
The past few decades have seen great progress in the exploration of nanoparticles (NPs) as novel tools for cancer treatments and diagnosis. Practical and reliable application of nanoparticle-based technology in clinical transformation remains nevertheless an ongoing challenge. The design, preparation and evaluation of various smart NPs with specific physicochemical responses in tumor-related physiological conditions have been of great interests in both academic and clinical research. Of particular, smart enzyme-responsive nanoparticles can predictively and selectively react with specific enzymes expressed in tumor tissues, leading to targeted delivery of anti-tumor drugs, reduced systemic toxicity and improved therapeutic effect. In addition, NPs interact with internal enzymes usually under mild conditions (low temperature, aqueous media, neutral or close to neutral pH) with high efficiency. In this review, recent advances in the past five years in enzyme-responsive nanoparticles for anti-tumor drug delivery are summarized and discussed. The following contents are divided based on the different action sites of enzymes towards NPs, notably hydrophobic core, cleavable/uncleavable linker, hydrophilic crown and targeting ligand. Enzyme-engaged destruction of any component of these delicate nanoparticle structures could result in either targeting drug delivery or controlled drug release.